An Analysis 5G Network Latency for Upload and Download: Case Study of 5G Network in Medan City - Hulu, Fitria Nova; Rusdi, Muhammad; Yadi, Indra (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
This research analyzes 5G network latency for upload and download activities in Medan City. Using a quantitative approach, data is collected through latency measurements at various test points throughout the city. Measurements are carried out with special network test tools that are able to detect latency accurately. The research results show that the average data speed for download activities is 14.62 Mbps while uploading is 22.72 Mbps, with an average latency value of 46.6 ms from the combined upload and download processes. Latency variability was also analyzed based on location and time factors, showing that the city center area had lower latency than the suburbs. This study indicates that the implementation of edge computing technology can further optimize 5G network performance in Medan City. These findings are important for telecommunications service providers to improve service quality and user experience